Canonical Correlation Analysis on the Association Between Sleep Quality and Nutritional Status Among Centenarians in Hainan - Liu, Guangdong; Yang, Shanshan; Liu, Wei; Wang, Shengshu; Tai, Penggang; Kou, Fuyin; Jia, Wangping; Han, Ke; Liu, Miao; He, Yao (Frontiers in Public Health, 2020)
Objective: To analyze the correlation between nutritional status and sleep quality among centenarians. Methods: A total of 1002 centenarians in Hainan were included in the full sample survey. The Mini Nutritional Assessment – Short Form (MNA-SF) was used for nutritional risk assessment and the Pittsburgh Sleep Quality Index Scale (PSQI) was used for evaluating sleep quality. Canonical correlation analysis was conducted to analyze their correlation. Results: Two statistically significant (P <0.05) canonical coefficients were found, with the first canonical correlation coefficient having a value of 0.247, eigenvalue of 0.065, and contribution rate of 89.0%. The linear combination of nutrition variable V1, mainly determined by MNA1 (appetite loss), MNA5 (dementia / depression), and MNA2 (weight loss), indicates an association with sleep quality; the linear combination of sleep quality W1, mainly determined by PSQI1 (subjective sleep quality), PSQI7 (daytime dysfunction), and PSQI2 (sleep latency), indicates an association with nutritional status. Appetite loss, dementia / depression, and weight loss have negative correlations with subjective sleep quality and daytime dysfunction. Conclusion: Among centenarians, the relationship between nutritional status and sleep quality is bidirectional. Furthermore, appetite loss, dementia/depression, weight loss, subjective sleep quality and daytime dysfunction are the main relevant factors.